Dynamic Changes in Bladder Morphology Over Time in Cervical Cancer Patients. (31st May 2021) - Jin, Fu; Liu, Qiang; Luo, Huanli; Zhu, Rui; Mou, Yanhong; Wu, Yongzhong; Wang, Ying
Objectives: Continuous surveillance of bladder volume (BV) is beneficial during the treatment of various urogenital diseases because the bladder is always changing its position, size and even shape at different filling phases. For this purpose, we quantified the motion of the urinary bladder. Methods: Daily ultrasound measurements and weekly cone-beam computed tomography scans were obtained from 89 patients in the supine position. BV, bladder centroid positions, and triaxial lengths in the left-right (LR), anterior-posterior (AP), and superior-inferior (SI) directions were compared across different time points. Results: BV linearly increased over time, and the mean urinary filling rate ( vtot ) was correlated with the patients' age and water consumption. The greatest bladder centroid motion occurred longitudinally, with less movement observed laterally. The maximum bladder centroid movement was 18.8 ± 2.2 mm inferiorly and 1.8 ± 0.9 mm posteriorly for every 10% decrease in BV. The rates of changes in triaxial lengths differed across the 4 filling phases. The rate was the largest at a BV range of 10-80 mL, especially in the LR direction, with values of 5.9 ± 1.0, 3.6 ± 1.0, and 3.9 ± 1.0 mm per every 10-mL BV increase for LR, AP, and SI, respectively. With bladder filling (<80 mL), the maximum increase in triaxial length was observed in the SI direction and the rates of all changes considerably decreased, especially at BV > 600 mL. Conclusion: The vtot could be used to evaluate the temporal changes in the bladder. The spatial changes should be assessed according to different filling phases based on the centroid position and triaxial lengths.